Sudden cardiac death in the adolescent population: a narrative review - Meet A. Patel; Anisha Malhotra; Franck H. Moussinga Mpondo; Vasu Gupta; Rahul Jain; Sachin Gupta; Rohit Jain (SpringerOpen, 2023)
Abstract Background Death from unexpected circulatory arrest within 60 min of onset of symptom is known as sudden cardiac death (SCD). In spite of the advancement in treatment and prevention strategies, SCD remains the most common cause of death worldwide especially in the young. Main body This review focuses on highlighting how different cardiovascular diseases contribute to SCD. We discuss the clinical symptoms that the patient experience prior to sudden cardiac arrest and the treatment strategies including pharmacological and surgical treatment. Conclusions We conclude that since there are many causes of SCD and very few treatment options, prevention strategies, early detection, and resuscitation of those at greatest risk is important.